Improving long-term postoperative pain monitoring and follow-up for women undergoing incontinence mesh surgery: a quality improvement initiative - Sissel Hegdahl Oversand; Tomislav Dimoski; Rune Svenningsen (BMJ Open Quality)
Background Stress urinary incontinence (SUI) affects many women, often resulting from childbirth-related injuries. Synthetic mesh SUI implants, popular since the 1990s, are effective but have raised concerns due to complications like long-term pain. In Norway, insufficient follow-up and inconsistent pain registration hinder accurate prevalence estimates. This study aimed to enhance pain registration and standardise follow-ups after sling surgery.Local problem Routine 3-year postoperative controls, recommended by the Norwegian Female Incontinence Registry (NFIR) have been deprioritised by public hospitals for financial reasons. Less than 50% of patients undergoing sling surgeries in 2017 received follow-ups, with only half including pain data. This risks underestimating pain prevalence and impedes quality improvements.Methods A quality improvement project (2022–2023), initiated by NFIR, included seven hospitals selected for surgical volume, location and follow-up performance. Interventions: (1) Structured 3-year telephone follow-ups with pain registration for SUI mesh surgeries between 1 April 2019 and 31 March 2020. (2) Mandatory clinical examinations for patients reporting persistent pain. (3) Improved NFIR pain monitoring to track onset and persistence. (4) Standardised patient information on postoperative pain.The NFIR pain variable was refined, with main data analyses at baseline, mid-project and finalisation.Results Follow-up rates exceeded 80%, with pain data documented for all. Persistent pain was self-reported by 4.3%. After clinical evaluations, 1.9% could be attributed to the mesh implant. Three patients (0.7%) required treatment, one needed partial mesh removal. Interdepartmental follow-up variability decreased, and NFIR pain monitoring was revised for precision.Conclusions Telephone-based follow-ups improved pain documentation and reduced departmental variability. Although pain prevalence was low, systematic follow-ups and refined monitoring remain crucial. Future efforts should explore electronic follow-ups and maintain interdepartmental collaboration, providing a model for similar healthcare challenges.